CHARACTERISTICS OF CREATIVE ACTIVITY AS A MEANS OF FORMING FUNCTIONAL COMPETENCE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
In this article the characteristic of creative activity as a way of formation of students functional competence is described.
Keywords: creative activity; competence